2017
DOI: 10.1016/j.neuron.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Hallmarks of Alzheimer’s Disease in Stem-Cell-Derived Human Neurons Transplanted into Mouse Brain

Abstract: Human pluripotent stem cells (PSCs) provide a unique entry to study species-specific aspects of human disorders such as Alzheimer's disease (AD). However, in vitro culture of neurons deprives them of their natural environment. Here we transplanted human PSC-derived cortical neuronal precursors into the brain of a murine AD model. Human neurons differentiate and integrate into the brain, express 3R/4R Tau splice forms, show abnormal phosphorylation and conformational Tau changes, and undergo neurodegeneration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
176
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(185 citation statements)
references
References 59 publications
9
176
0
Order By: Relevance
“…Our most significant DMP resided in BNC1 (cg26429925; standardized regression coefficient = -0.75, p = 4.71E-06). Differential methylation of BNC1, which encodes a zinc finger protein basonuclein, has been previously found in frontal cortex of AD subjects compared with controls [31], and upregulation of BNC1 has been observed in a novel chimeric model of AD [32].…”
Section: Resultsmentioning
confidence: 85%
“…Our most significant DMP resided in BNC1 (cg26429925; standardized regression coefficient = -0.75, p = 4.71E-06). Differential methylation of BNC1, which encodes a zinc finger protein basonuclein, has been previously found in frontal cortex of AD subjects compared with controls [31], and upregulation of BNC1 has been observed in a novel chimeric model of AD [32].…”
Section: Resultsmentioning
confidence: 85%
“…However, none of the neurons die in culture, as seen in AD patients [8,92]. Recently, it was reported that healthy neurons from hiPSC degenerate if transplanted in PD model mouse brains, suggesting that amyloid plaques from the diseased environment are responsible for neural degeneration [93].…”
Section: Using Pscs For Modeling Neurovascular Diseasementioning
confidence: 99%
“…Recently a unique chimeric human-mouse model was developed by transplanting stem-cell-derived human cortical neurons into mouse brain. [194] Remarkably, the new mice showed that A β species generated in the brain can induce AD hallmarks, including tau hyperphosphorylation, neurite dystrophy, and cell death in non-manipulated human neurons. This study highlights the unmet need for engineering more physiologically relevant matrices that could fully recapitulate the natural ECM architecture and function.…”
Section: Designing Synthetic Matrices For Recapitulating the Extramentioning
confidence: 99%